Salivary Electrochemical Cortisol Biosensor Based on Tin Disulfide Nanoflakes - Liu, Xinke (Nanoscale Res Lett, 2019)
Cortisol, a steroid hormone, is secreted by the hypothalamic-pituitary-adrenal system. It is a well-known biomarker of psychological stress and is hence known as the “stress hormone.” If cortisol overexpression is prolonged and repeated, dysfunction in the regulation of cortisol eventually occurs. Therefore, a rapid point-of-care assay to detect cortisol is needed. Salivary cortisol electrochemical analysis is a non-invasive method that is potentially useful in enabling rapid measurement of cortisol levels. In this study, multilayer films containing two-dimensional tin disulfide nanoflakes, cortisol antibody (C-M(ab)), and bovine serum albumin (BSA) were prepared on glassy carbon electrodes (GCE) as BSA/C-M(ab)/SnS(2)/GCE, and characterized using electrochemical impedance spectroscopy and cyclic voltammetry. Electrochemical responses of the biosensor as a function of cortisol concentrations were determined using cyclic voltammetry and differential pulse voltammetry. This cortisol biosensor exhibited a detection range from 100 pM to 100 μM, a detection limit of 100 pM, and a sensitivity of 0.0103 mA/Mcm(2) (R(2) = 0.9979). Finally, cortisol concentrations in authentic saliva samples obtained using the developed electrochemical system correlated well with results obtained using enzyme-linked immunosorbent assays. This biosensor was successfully prepared and used for the electrochemical detection of salivary cortisol over physiological ranges, based on the specificity of antibody-antigen interactions.